313 Interaction of Inflammation and Hyperoxia in Neonatal White Matter Damage. (October 2012) - Brehmer, F; Bendix, I; Looij, Y van de; Sifringer, M; Sizonenko, S; Mallard, C; Bührer, C; FelderhoffMüser, U; Gerstner, B
Abstract : Intrauterine infection/inflammation are major causes of preterm birth. The dramatic rise of oxygen tissue tension compared to intrauterine conditions amounts to relative hyperoxia in preterm infants. Both, infection/inflammation and hyperoxia have been shown to be involved in brain injury of preterm infants. Hypothesizing an additive or synergistic effect, we investigated the influence of a systemic lipopolysaccharide (LPS) application on hyperoxia-induced white matter damage (WMD) in newborn rats. Three-day-old Wistar rat pups received 0.25 mg/kg LPS i.p. and were subjected to 80% oxygen on P6 for 24 hrs. WMD was assessed by immunohistochemistry, western blot and diffusion tensor magnetic resonance imaging. In addition, LPS and hyperoxia were studied in an in vitro co-culture system of primary rat oligodendrocytes and microglia cells. Both noxious stimuli, hyperoxia and LPS, induced a significant increase in apoptotic cell death as revealed by elevatation of cleaved caspase-3 and TUNEL-positive cells. Furthermore, both hyperoxia and LPS caused hypomyelination, as revealed by western blot, immunohistochemistry and altered WM microstructure on MRI. However, the combination of hyperoxia and LPS did neither increase nor decrease cell death and hypomyelination in vivo. In contrast, LPS pre-incubation reduced oligodendrocyte susceptibility towards hyperoxia in vitro. Our data suggest that inflammation and hyperoxia strongly attenuate oligodendrocyte maturation by apoptotic and non-apoptotic pathways. If both insults are combined, second phase releases of protective cytokines can partially prevent oligodendrocyte cell death. The knowledge of interactions between inflammation and hyperoxia might offer new therapeutic opportunities to prevent WMD in preterm infants.